Public relations excellence in crisis communication management: a case study in Tenaga Nasional Berhad / Saidathul Nizah Mat Tazin - Mat Tazin, Saidathul Nizah (2018)
Contributions by government-linked companies (GLCs) to national development once threatened by multiple types of crises, which have the probability of tarnishing reputation and stakeholders' trust. This study aims to investigate the significance of public relations excellence in managing crisis communication in Tenaga Nasional Berhad (TNB), an organisation involved in the Government Linked Company Transformation Program (GLCTP) to deliver high performance. TNB has experienced several crises since its establishment. The objectives of this study are to examine what is management’s acceptance of public relations empowerment in crisis management, to explain the strategic management approach in crisis communication management by the Corporate Communication Department, to assess the effectiveness of crisis communication in TNB through a comparison of organisational response to stakeholder reactions and to recommend the best practices of crisis communication management in TNB. This study analyses the crisis communication process in TNB and will be a reference to develop strategic crisis communication planning in organisations in Malaysia, especially GLCs.This study is an intrinsic case study to better understand a particular case in its world context (in Denzin & Lincoln, 2000 & Yin, 2011). It focuses on selected generic characteristics of the Excellence Theory (Grunig, 1992) to study public relations practice in crisis communication management. Herrero-Gonzalez and Pratt’s (1996) Integrated Symmetrical model is applied as a theoretical framework for crisis communication management.